2010
DOI: 10.1074/jbc.m110.104968
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Putidaredoxin Reductase·Putidaredoxin Electron Transfer Complex

Abstract: In the camphor monooxygenase system from Pseudomonas putida, the [2Fe-2S]-containing putidaredoxin (Pdx) shuttles electrons between the NADH-dependent putidaredoxin reductase (Pdr) and cytochrome P450 cam . The mechanism of the Pdr⅐Pdx redox couple has been investigated by a variety of techniques. One of the exceptions is x-ray crystallography as the native partners associate weakly and resist co-crystallization. Here, we present the 2.6-Å x-ray structure of a catalytically active complex between Pdr and Pdx C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…This is supported by a computer model of the PdR-Pdx complex (52), mutagenesis studies of the PuR/Pux interaction (14), the crystal structures of BphA4-BphA3 complexes (51), and the crystal structures of cross-linked PdR-Pdx and AdR-Adx (28,53). The si side surfaces of ONFRs structurally characterized to date have largely positive electrostatic potential surrounding a central patch of neutral residues located directly above the FAD isoalloxazine ring (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This is supported by a computer model of the PdR-Pdx complex (52), mutagenesis studies of the PuR/Pux interaction (14), the crystal structures of BphA4-BphA3 complexes (51), and the crystal structures of cross-linked PdR-Pdx and AdR-Adx (28,53). The si side surfaces of ONFRs structurally characterized to date have largely positive electrostatic potential surrounding a central patch of neutral residues located directly above the FAD isoalloxazine ring (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…KKS102, have been reported (28,51). Recently, the structure of a covalently cross-linked PdR-Pdx complex (via Lys 409 and Glu 72 ) has been solved, and the resultant investigations indicated that there is a high degree of fine tuning in the protein/ protein interactions to allow efficient electron transfer (53,71). The crystal structures of PuR and PuxB have also provided insight into the recognition interactions (14,15,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14). The enzymes differ on the route followed by electrons from the Fe-S cluster to FAD, with some of them involving several intermediate residue side chains [152]. Additionally, Fig.…”
Section: Ec 1161: Oxidoreductases Of Metal Ionsmentioning
confidence: 99%
“…Our results suggested also that the inter-protein electron transfer could proceed via different pathways that likely include Asp38 and Cys39 but do not involve Trp106. This initial effort has been followed by successful production of a functional covalent Pdr-Pdx complex [43], whose crystal structure was determined to 2.6 Å resolution [44] and experimentally tested [45]. …”
Section: Pdx-pdr Redox Pairmentioning
confidence: 99%